Geomagnetism during solar cycle 23: Characteristics - Jean-Louis Zerbo (Journal of Advanced Research, 2013)
On the basis of more than 48 years of morphological analysis of yearly and monthly values of the sunspot number, the aa index, the solar wind speed and interplanetary magnetic field, we point out the particularities of geomagnetic activity during the period 1996–2009. We especially investigate the last cycle 23 and the long minimum which followed it. During this period, the lowest values of the yearly averaged IMF (3 nT) and yearly averaged solar wind speed (364 km/s) are recorded in 1996, and 2009 respectively. The year 2003 shows itself particular by recording the highest value of the averaged solar wind (568 km/s), associated to the highest value of the yearly averaged aa index (37 nT). We also find that observations during the year 2003 seem to be related to several coronal holes which are known to generate high-speed wind stream. From the long time (more than one century) study of solar variability, the present period is similar to the beginning of twentieth century. We especially present the morphological features of solar cycle 23 which is followed by a deep solar minimum.